A Cost Efficiency Analysis of Boro Rice Production in Dinajpur District of Bangladesh - Md Shajedur Rahaman; Sadika Haque; Md Abdur Rouf Sarkar; Mohammad Chhiddikur Rahman; Md Salim Reza; Mohammad Ariful Islam; Md Abu Bakr Siddique (Fundamental and Applied Agriculture, 2021)
The size of the farm is an important factor that reflects the efficient utilization of resources in farming. Therefore, this paper aims to investigate how the farm size affects the cost efficiency of rice production during the Boro season in Bangladesh. In particular, the analysis aims to estimate the concentration of cost efficiency among the 240 small, medium, and large Boro rice growers sampled in the Dinajpur district. Descriptive statistics were used to evaluate the socioeconomic characteristics of rice farmers. A Cobb-Douglas type stochastic cost frontier model was employed to figure out how the rice farmers are cost-efficient. The sociodemographic factors that affect efficient investment in rice production also have been identified. The results of the study show a broad range of cost efficiency scores between 56.65 to 96.40% for the worse to the best rice-growing farmer, respectively with an average efficiency of 84.01%. The findings also show that the mean cost efficiency level of small, medium, and large farmers was 83.30, 85.58, and 94.43%, respectively. The land rental fees, human labor wages, irrigation prices, and pesticide prices are the key factors that contribute to the productivity of rice cultivation. The relatively higher level of cost efficiency among large farmers obviously demonstrates the notion that only large farmers in the study region are investing efficiently in rice growing. Irrespective of the farm size, the cost efficiency drivers found out that more efficient were the farmers who had more experience in farming, obtained training on rice production techniques, and better access to institutional credit. It is therefore recommended that rice farmers should be well trained, provided credit access along with developing rural set-up, and also provide extension services in order to increase the cost efficiency levels in Boro season.
Keywords: 330; Cost effective; Rice; Farm size; Stochastic frontier analysis